Physical and biochemical parameters of fresh and dry ginger (Zingiber officinale Roscoe) - R Visvanathan, E Jayashree, (Journal of Spices and Aromatic Crops, 2011)
The physical and biochemical properties of fresh and dry ginger (Zingiber officinale) (cv: Himachal) obtained from Nemmara (Palakkad District, Kerala), useful for the design of processing machineries, were determined. The average moisture content of fresh and dry rhizomes were 81.70% and 8.85%, respectively. The average length, width and thickness of fresh rhizome were 14.99 cm, 8.17 cm and 4.49 cm, respectively and the corresponding values for dry rhizome were 9.74 cm, 5.56 cm and 4.49 cm. The mean values of cylindricity for primary, secondary and tertiary finger rhizomes were 0.46, 0.51 and 0.56, respectively and the corresponding values for dry finger rhizomes were 0.48, 0.53 and 0.58. The average mass, volume and surface area of fresh rhizomes were 103.45 g, 85.0 cm3 and 194.52 cm2, respectively and the corresponding values for dry rhizomes were 31.62 g, 22.10 cm3 and 65.84 cm2. The bulk density, true density and porosity for fresh rhizomes were determined as 471.49 kg m-3, 1107.01 kg m-3 and 66.80%, respectively, and for dry rhizomes the values were 460.09 kg m-3, 1013.22 kg m-3 and 54.09%. The angle of repose increased from 34.6° to 39.5° after drying. Mild steel surface offered more frictional resistance than other surfaces and the coefficient of friction for fresh and dry ginger against mild steel was 0.74 and 0.54, respectively. The average meat : peel ratio of the whole fresh rhizome was 10.7:1. The average recovery of dry ginger was 23.01%. The dry ginger obtained had 1.6% essential oil, 3.5% oleoresin and 2.7% crude fibre.